Circular polarization antenna for CW V-band radar - Kashin, S. V. (Видавництво Національного університету "Львівська політехніка", 2009)
Practical realization of the circular polarization antenna for CW V-band radar is described.
Keywords: antenna; radar; orthomode transducer; circular polarization